Revealing of elderly people with high risk of falling using complex geriatric assessment - G. V. Kiseleva; E. V. Frolova; A. V. Turusheva (Лечащий Врач)
The article analyzes the possibility of identifying a high risk of Falling in elderly patients using geriatric evaluation based on a computer program. According to the results of this study, the correlation between high risk of falling and geriatric syndromes was evaluated. For the first time, a high risk of falling in patients over 65 years old was detected using a computer web application for complex geriatric assessment. Measures have been developed to correct the risk of falling in the elderly and assess their effectiveness.